Genetic Association Study of KCNQ5 Polymorphisms with High Myopia. (13th August 2017) - Liao, Xuan; Yap, Maurice K. H.; Leung, Kim Hung; Kao, Patrick Y. P.; Liu, Long Qian; Yip, Shea Ping
Abstract : Identification of genetic variations related to high myopia may advance our knowledge of the etiopathogenesis of refractive error. This study investigated the role of potassium channel gene (KCNQ5) polymorphisms in high myopia. We performed a case-control study of 1563 unrelated Han Chinese subjects (809 cases of high myopia and 754 emmetropic controls). Five tag single-nucleotide polymorphisms (SNPs) of KCNQ5 were genotyped, and association testing with high myopia was conducted using logistic regression analysis adjusted for sex and age to give P a s y m values, and multiple comparisons were corrected by permutation test to give P e m p values. All five noncoding SNPs were associated with high myopia. The SNP rs7744813, previously shown to be associated with refractive error and myopia in two GWAS, showed an odds ratio of 0.75 (95% CI 0.63–0.90; P e m p = 0.0058) for the minor allele. The top SNP rs9342979 showed an odds ratio of 0.75 (95% CI 0.64–0.89; P e m p = 0.0045) for the minor allele. Both SNPs are located within enhancer histone marks and DNase-hypersensitive sites. Our data support the involvement of KCNQ5 gene polymorphisms in the genetic susceptibility to high myopia and further exploration of KCNQ5 as a risk factor for high myopia.